Association of Helicobacter pylori infection and white blood cell count: a cross-sectional study - Yang Yang; Xue Wu; Qiang Wang; Yahong Wang; Haiying Wang; Yanli Zhu; Rui Jiao; Xiaojuan Ma; Xiaoqing Guo; Shaofei Zhang (BMJ Open)
Introduction Helicobacter pylori is a type of Gram-negative microaerobic bacteria that inhabits the gastric mucosal epithelium. It can cause various gastrointestinal diseases including gastritis, peptic ulcer and gastric cancer. White blood cells (WBC) are common immune cells, the increase in whose countoften indicates the presence of an infection. Currently, the relationship between H. pylori and WBC count remains full of controversy. This study aims to further elucidate the effects of H. pylori on WBC count in a population undergoing physical examination.Methods and analysis A total of 864 participants who underwent physical examination and 14C urea breath test (UBT) were retrospectively enrolled in this study from January to June 2021. The overall population was divided into H. pylori-negative (Hp−) and H. pylori-positive (Hp+) groups based on the disintegration per minute (DPM) value detected by UBT. Spearman’s correlation analysis was used to assess the correlation between DPM and WBC count. General linear regression models were applied to assess the potential factors contributing to the increase in WBC count. Generalised additive model (GAM) was performed to identify the non-linear relationship between DPM and WBC count. Additionally, a piecewise linear regression was used to examine the threshold effect of the DPM on WBC count.Results 403 subjects were diagnosed with H. pylori infection. The WBC and platelet (PLT) counts in the Hp+ group were significantly higher than those in the Hp− group. Additionally, the prevalence of H. pylori infection gradually increased with the WBC count quartiles (38.89% and 54.67% in quartile 1 and quartile 4, respectively). Spearman’s correlation analysis showed that the DPM value significantly correlated with WBC count (r=0.089, p=0.009) and PLT count (r=0.082, p=0.017). The linear model revealed a positive independent association of H. pylori infection and DPM with WBC count (βHp+=0.398 (95% CI 0.170, 0.625), p<0.001; βDPM=0.002 (95% CI 0.000, 0.0030), p=0.018). The results of the GAM and the piecewise linear regression suggested that the cut-off points of the association between DPM and WBC count were 40 and 155 of DPM, that is, the effect of DPM on WBC count varied with the difference of DPM <40, 40–155, and >155 (βDPM=−0.005 (95% CI −0.017, 0.007), p=0.423; βDPM=0.006 (95% CI 0.002, 0.013), p=0.047; and βDPM=−0.007 (95% CI −0.012, –0.002), p=0.004, respectively).Conclusions H. pylori infection was independently and positively correlated with WBC count; however, the effect of DPM on WBC count varied across different WBC count intervals, suggesting distinct immunological responses at different stages of infection.